Trisentra Pendidikan Anak Menuju Langkah Awal Pengabdian Besar: Studi Kasus: KKN Kelompok 4 di Kp. Tapos Udik RT. 001/ RW. 002 Desa Tapos 1 Kecamatan Tenjolaya Kabupaten Bogor - Somantri, Fikri Indriana; Suryana, Agus; Ery Subaeri; Herlina, Herlina; Maulana, Dede Maulana; Adawiyah, Siti Robiyatul; Billa, Keisya; Nuraeni, Nuraeni; Annisa Fatmala; Khoeriyah, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Children's education is a key foundation for national development, with the quality of the younger generation heavily influenced by the roles of family, school, and community. The concept of the Three Centers for Child Education, initiated by Ki Hadjar Dewantara, emphasizes the importance of synergy between these three educational centers to shape a generation with character, intelligence, and a dedication to service. This study aims to analyze the roles of family, school, and community in children's education and identify possible synergies in Tapos 1 Village, Tenjolaya District, Bogor Regency. The study employed a qualitative approach with a case study method. Data were collected through observation, informal interviews, and documentation during the Community Service Program (KKN) at IAI-N Laa Roiba. Data analysis was conducted using thematic techniques, grouping information into key themes: the role of family, school, community, and synergy between centers. The results show that families remain the primary educators, although the level of involvement varies. Schools serve as centers of knowledge and skills, but face limitations in facilities and curriculum burdens. The community contributes through social, cultural, and religious activities, but coordination with families and schools remains weak. Community Service Program activities have been proven to act as a catalyst, strengthening communication and collaboration between centers, producing children who are more confident, disciplined, and possess greater social empathy. This research provides a theoretical contribution to strengthening the literature on the implementation of the Trisentra Pendidikan concept in the digital era, as well as a practical contribution for families, schools, and communities to develop collaborative educational patterns. Thus, the synergy of the Trisentra Pendidikan Anak (Children's Education Center) is a crucial strategy in preparing the nation's next generation to be intelligent, character-driven, and service-oriented.